Oxford Reading Tree TreeTops Fiction: Level 15 More Pack A: The Worst of the Vikings level 15 more pack A : the worst of the vikings - McAllister, Margaret; Anderson, Scoular ([S.l.] : Oxford University Press, 2014)
Three useless Vikings are rowing towards Britain in The Worst of the Vikings. Morbid hates fighting, Vapid is not sure what pillaging is and Torpid just wants to go back to sleep. Is their leader, Harald Hairyhands, wise to send them into battle? TreeTops Fiction contains a wide range of quality stories enabling children to explore and develop their own reading tastes and interests. It contains stories from a variety of genres including humour, sci-fi, adventure, mystery and historical fiction. These exciting stories are ideal for introducing children to a wide selection of authors and illustrators. There is huge variety to ensure every reader finds books they will enjoy and can read. Books contain inside cover notes to support children in their reading. Help with children's reading development also available at www.oxfordowl.co.uk. The books are finely levelled, making it easy to match every child to the right book.